Continuity of medication management and continuity of care: Conceptual and operational considerations. (9th December 2014) - Beadles, Christopher A; Voils, Corrine I; Crowley, Matthew J; Farley, Joel F; Maciejewski, Matthew L
Objective: Continuity of care is considered foundational to high-quality care. Traditional continuity of care constructs may adequately characterize care quality in general populations, but may merit reconceptualization for patients with multiple chronic conditions. Specifically, interactions between multiple chronic condition patients and providers involve complex medication management; therefore care continuity measurement may be more relevant if focused on the provider subset who prescribes essential medications for chronic conditions—a construct we call continuity of medication management. Our objective was to explore conceptual distinctions between continuity of medication management and continuity of care, survey existing evidence in this area, and discuss implications of our findings for future research and intervention development. Methods: In this topical review, we discuss conceptual distinctions between continuity of medication management and continuity of care, review the limited continuity of medication management–related empirical evidence, and discuss implications for future research and interventions. Results: Continuity of medication management represents a potential conceptual and measurement advance by reflecting interpersonal continuity and management continuity, and may provide a means of identifying patients at high-risk of adverse events. Empirical evidence also establishes support for continuity of medication management as a meaningful measure of care continuity. Finally, continuity of medication management may also be a potential target for future intervention to improve care delivery among multiple chronic condition patients. Conclusion: If continuity of medication management is validated in diverse populations, correlated with patient outcomes, and responsive to change, then it may be an important target for improving the health and health care of multiple chronic condition patients.